2018
DOI: 10.5505/ejm.2018.70893
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Multiforme; Sixty Six Case Series with Review of Literature

Abstract: Erythema multiforme (EM) is an acute, self-limited, and sometimes recurrent skin disease considered to be a hypersensitivity reaction associated with certain medications and infections. EM has recently been recognized as a distinct disease differentiated from the Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). The aim of this study was to evaluate the clinical and histopathological characteristics of patients with EM. The retrospective study included 66 patients who received outpatien t or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
2
7
0
2
Order By: Relevance
“…It is also consistent with the results of the study that was carried out by Lerch M et al 1 who have stated that EM is particularly seen in the second and third decades of life. The current study revealed that 7 of our patients with EM were females and these results are in agreement with the results of Yavuz IH et al 21 who had also reported a higher percentage of EM among females (66.7% of their patients were females). The findings were also consistent with Samim F et al 22 who indicated EM is more common in women than men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is also consistent with the results of the study that was carried out by Lerch M et al 1 who have stated that EM is particularly seen in the second and third decades of life. The current study revealed that 7 of our patients with EM were females and these results are in agreement with the results of Yavuz IH et al 21 who had also reported a higher percentage of EM among females (66.7% of their patients were females). The findings were also consistent with Samim F et al 22 who indicated EM is more common in women than men.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study demonstrated that the mean age of the studied sample with ORF was 36.1 years. In addition, our findings revealed that 7 out of 9 patients with EM were less than 40 years of age and these findings are consistent with the finding of the study that was conducted by Yavuz I H et al 21 where they also found that the mean age of their patients with EM was 36.7 years. It is also consistent with the results of the study that was carried out by Lerch M et al 1 who have stated that EM is particularly seen in the second and third decades of life.…”
Section: Discussionsupporting
confidence: 92%
“…Erythema multiforme occurs in patients of all ages but is most prevalent in adolescents and young adults (the peak age of 20–40 years), 1 , 7 , 8 more often in male (male-to-female ratio of 2 to 3:1). 4 , 8 There are several precipitating factors associated with the development of EM, including infections (nearly 90% cases) and medications (10% cases).…”
Section: Discussionmentioning
confidence: 99%
“…Erythema multiforme (EM) is a rare immune-mediated mucocutaneous disorder with acute onset, sometimes recurrent, and sometimes self-limited. 1 , 2 The two main forms of EM are EM major with the involvement of two or more mucosal sites and EM minor with the involvement of one or none mucosal site. 3 The etiology of EM remains unknown, but infections, certain drugs, immune conditions, and malignancies can trigger the development of this condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation